2015
DOI: 10.3400/avd.oa.15-00069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Optimal Timing of Endovascular Treatment for Type B Aortic Dissection

Abstract: Hajime Kinoshita and Eiki Fujimoto equally contributed to this work. Objectives:To determine the efficacy and the optimal timing of thoracic endovascular aortic repair (TEVAR) for closing the primary entry in uncomplicated patients with chronic type B aortic dissection and a patent false lumen (FL). Methods: Thirteen patients underwent TEVAR for aortic dissection between 2008 and 2012. These patients had chronic dissection with a patent FL and expansion of the aorta. Early TEVAR was performed for five patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Many investigators emphasize that the most appropriate timing of preemptive TEVAR is ≤6 months after onset. 1287,1295,[1368][1369][1370]1374,1375 This timing is also consistent with the period when favorable thoracoabdominal remodeling of a false lumen after TEVAR is achieved, supporting the recommendation. On the other hand, an RCT of preemptive TEVAR in the acute phase did not verify its superiority to medical treatment for the prognosis one year after TEVAR, being contrary to the above opinion.…”
Section: B Endovascular Treatment I Indications Of Preemptive Tevarsupporting
confidence: 60%
See 1 more Smart Citation
“…Many investigators emphasize that the most appropriate timing of preemptive TEVAR is ≤6 months after onset. 1287,1295,[1368][1369][1370]1374,1375 This timing is also consistent with the period when favorable thoracoabdominal remodeling of a false lumen after TEVAR is achieved, supporting the recommendation. On the other hand, an RCT of preemptive TEVAR in the acute phase did not verify its superiority to medical treatment for the prognosis one year after TEVAR, being contrary to the above opinion.…”
Section: B Endovascular Treatment I Indications Of Preemptive Tevarsupporting
confidence: 60%
“…1287, 1289 The selection of patients and timing of intervention are controversial. 385,[396][397][398][399][400]1267,[1287][1288][1289][1290][1291][1292]1295,[1368][1369][1370] Patients to be selected are those with enlargement of the false-lumen and are at risk of rupture during the chronic phase with conventional medical therapy. The condition is also termed "high-risk uncomplicated dissection".…”
Section: Initial Treatment After Diagnosismentioning
confidence: 99%
“…[8][9][10] Early TEVAR for chronic type B dissection with a patent false lumen result in a good prognosis and favorable aortic remodeling. [11] For patients with uncomplicated type B acute aortic syndrome, antihypertensive treatment rather than surgery is acceptable for initial management. [12] However, results from the INSTEAD-XL trial encourage the use of TEVAR in patients with stable type B aortic dissection and suitable anatomy due to optimal long-term benefit.…”
Section: Discussionmentioning
confidence: 99%
“…TEVAR within 1 month after the index dissection has been shown to be inferior to optimal medical management, with a higher all-cause death and aorta-specific mortality. 38 TEVAR within 3 months has been shown to have more favorable aortic remodeling. 39 Fanelli et al confirmed the results of others and found a higher capacity of remodeling of acute rather than of chronic dissection after TEVAR, along with a lower false lumen thrombosis rate in chronic compared with acute dissection.…”
Section: Discussionmentioning
confidence: 99%